Analisis Kebutuhan Pelatihan - Apriani Sri Mulyani; Azzahra Oktaviani; Dinda Ayu; Machdum Bachtiar (PT Ilmu Data Indonesia, 2026)
This study discusses the importance of Training Needs Analysis (TNA) in human resource development as a strategic effort to improve organizational performance. Training Needs Analysis is conducted through several systematic stages, including the identification of organizational goals, employee performance analysis, task and competency analysis, individual analysis, and the determination of training priorities and plans. The study uses a library research method by reviewing various relevant literature related to human resource management, employee competency development, and organizational training systems. The findings show that a systematic and data-driven Training Needs Analysis enables organizations to design training programs that are more targeted, effective, and aligned with organizational strategies and objectives. In addition, the analysis helps organizations identify competency gaps, improve employee productivity, and support sustainable organizational development in a dynamic work environment. Effective training planning also contributes to increasing employee motivation, work efficiency, and adaptability to technological and organizational changes. Furthermore, understanding employee performance and competencies plays an important role in ensuring that training programs are implemented according to actual organizational needs. Therefore, Training Needs Analysis can be considered an essential foundation in creating high-quality human resources that are capable of supporting organizational competitiveness and long-term success. The study concludes that organizations should continuously conduct training needs assessments to ensure the relevance and effectiveness of human resource development programs in facing evolving workplace challenges.